Multiparametric nanoparticle-induced toxicity readouts with single cell resolution in HepG2 multicellular tumour spheroids. Issue 41 (18th October 2021) - Kelly, Suainibhe; Byrne, Maria H.; Quinn, Susan J.; Simpson, Jeremy C.
Abstract : A platform for large-scale profiling of nanoparticle-induced toxicity in multicellular tumour spheroids, providing quantitative information from multiple organelles using high-content analysis. Abstract : The use of nanomaterials as therapeutic delivery vehicles requires their careful pre-clinical evaluation. Of particular importance in this regard is measurement of cellular toxicity, ideally assessing multiple parameters in parallel from various relevant subcellular organelles. In recent years it has become evident that in vitro monolayer-grown cells do not always accurately predict any toxicity response seen in vivo, and so there is a need for more sophisticated in vitro cell models, employing a greater depth of characterisation. In this work we present an automated high-content screening microscopy approach for quantifying nanoparticle-induced toxicity in a three-dimensional multicellular tumour spheroid (MCTS) cell model. As a proof-of-principle, we perform a comparative toxicity profile study of carboxylate- versus amine-modified polystyrene nanoparticles in HepG2 spheroids. Following treatment with these nanoparticle types, we demonstrate that several hundred spheroids, of various sizes, can be morphologically profiled in a single well using automated high-content image analysis. This provides a first level of information about spheroid health in response to nanoparticle treatment. Using a range of fluorescent reporters assessing membrane permeability, lysosome function and mitochondrial activity, we also show that nanoparticle-induced toxicity information can be obtained from individual cells with subcellular resolution. Strikingly, our work demonstrates that individual cells do not all behave in a consistent manner within a spheroid structure after exposure to nanoparticles. This highlights the need for toxicity studies to not only assess an appropriate number of spheroids, but also the importance of extracting information at the subcellular level.